2018
DOI: 10.1080/16549716.2018.1448250
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, socio-economic and behavioural correlates of BMI in middle-aged black men and women from urban Johannesburg, South Africa

Abstract: Background: There is a high and increasing prevalence of overweight and obesity in South Africans of all ages. Risk factors associated with overweight and obesity must be identified to provide targets for intervention. Objective: To identify the demographic, socio-economic and behavioural factors associated with body mass index (BMI) in middle-aged black South African men and women. Methods: Data on demographic and socio-economic factors were collected via questionnaire on 1027 men and 1008 women from Soweto J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
3
27
1
Order By: Relevance
“…Our findings are congruent with other studies from South Africa [59] and SSA [47, 56]. Although tobacco use is associated with low BMI, the use of tobacco should be discouraged as it is detrimental to health through the increased risk of lung cancer and cardiovascular diseases [60].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are congruent with other studies from South Africa [59] and SSA [47, 56]. Although tobacco use is associated with low BMI, the use of tobacco should be discouraged as it is detrimental to health through the increased risk of lung cancer and cardiovascular diseases [60].…”
Section: Discussionsupporting
confidence: 91%
“…lean, overweight and obesity between the six AWI-Gen Centres. In the accompanying set of papers, including one from each Centre, the risk factors and correlates with obesity were examined [7][8][9][10][11][12]. At five of the six study sites women had significantly higher BMI compared to men, whereas in Nanoro, men had higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Marital status: Being married or co-habiting is associated with higher BMI. Details for each study site are provided in the Special Issue [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the baseline data generated from this study has been demonstrated in several recent publications, including the identification of regional and sex differences in the prevalence of hypertension across SSA [60], and the six papers on BMI distribution in this special edition of Global Health Action [6772]. Manuscripts discussing the prevalence of diabetes, body composition and obesity, dyslipidemia, kidney disease, and smoking and alcohol consumption are currently in preparation.…”
Section: Discussionmentioning
confidence: 99%